Nouveaux et anciens espaces de circulation internationale au Maroc - Mehdi Alioua (Revue des Mondes Musulmans et de la Méditerranée)
Subsaharian transnational migrants going to Europe come from a variety of countries, have various motivations, may have experienced quite different situations. However, once away from home, they reorganize collectively in the stopping places which constitute steps in their long journey. In each of these stops and steps, they get to acknowledge their resemblance and to cooperate, thus progressively building up a common story, or “adventure”: the migration project and techniques they share make them share more.Once across the Sahara, the Subsaharian trans-migrants stick to the Maghrebi societies by grafting their own circulations on those of the local populations. In Morocco, the populations who deal with the passing and the more or less durable settling of these newcomers are the ones living in socioeconomic relegation areas, such as the poorer suburbs of Rabat, Casablanca or Tangiers; these populations know what migration is about, as they are themselves the product of a continuous arrival of inland migrants. The neighborhoods we studied therefore are constituted of a superposition of varied forms of mobility and migration logics and strategies. The analysis of such migration dynamics is a good platform from which to observe how the « bottom-up » introduction – by populations in constant mobility – of this alterity inside Maghrebi societies affects these societies, and their own cities.